Adolescent alcohol and cannabis use as risk factors for head trauma in the Northern Finland Birth Cohort study 1986 - Koivisto, Maarit K.; Puljula, Jussi; Levola, Jonna M.; Mustonen, Antti; Miettunen, Jouko; Alakokkare, Anni Emilia; Niemelä, Solja (European Journal of Public Health, 2023)
Background: The aim of this study was to assess the associations between cannabis use and frequency of alcohol intoxication in adolescence with the risk of traumatic brain injury and craniofacial fractures in early adulthood. Hypothesis was that using alcohol and cannabis in adolescence could increase the risk for head traumas. Methods: Data from the Northern Finland Birth Cohort 1986 (n = 9432 individuals) were used to investigate the prospective association between the self-reported frequency of alcohol intoxication (n = 6472) and cannabis use (n = 6586) in mid-adolescence and register-based, head trauma diagnoses by ages 32–33 years. To test the robustness of these associations, the statistical models were adjusted for a range of other confounders such as illicit drug use, previous head trauma and self-reported mental health problems. Results: In multivariate analyses, cannabis use was statistically significantly associated with a greater risk of traumatic brain injury among females [hazard ratio (HR) 1.9, 95% confidence interval (CI) 1.1–3.2, P = 0.024). Frequent alcohol intoxication was a statistically significant independent risk factor for both traumatic brain injury (HR 2.6, 95% CI 1.7–3.9, P < 0.001) and craniofacial fractures (HR 2.7, 95% CI 1.6–4.8, P < 0.001) among males. Conclusions: Cannabis use in adolescence appears to associate independently with elevated risk for traumatic brain injury among females, and frequent alcohol intoxication in adolescence seems to associate with elevated risk of both traumatic brain injury and craniofacial fractures among males. Peer reviewed